Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/ageing/afx135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating physical activity in dementia: a systematic review of outcomes to inform the development of a core outcome set

Abstract: the need for the development and implementation of a Core Outcome Set has been reinforced. Ahead of the completion of the Core Outcome Set, researchers and clinicians are advised to measure the impact of physical activity interventions on these frequently reported outcome domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…In line with Gonçalves et al [ 4 ], we encourage scientists and clinical practitioners to reach a consensus concerning the use of motor assessments, and to apply a standardised assessment procedure aiming to enhance comparability in the research field and clinical practice. With regard to scientific publications, we therefore ask scientists to give a detailed report on how they perform motor assessments in IWD, as different modifications exist and it is often not clear which has been applied.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In line with Gonçalves et al [ 4 ], we encourage scientists and clinical practitioners to reach a consensus concerning the use of motor assessments, and to apply a standardised assessment procedure aiming to enhance comparability in the research field and clinical practice. With regard to scientific publications, we therefore ask scientists to give a detailed report on how they perform motor assessments in IWD, as different modifications exist and it is often not clear which has been applied.…”
Section: Discussionmentioning
confidence: 58%
“…Designing studies to investigate the efficacy and effectiveness of physical activity on motor and cognitive performance in individuals with dementia (IWD) is challenging. Despite increasing research in this area [ 1 ], there still is insufficient evidence, which can be explained by methodological limitations, unspecific interventions, or inappropriate assessments [ 2 4 ]. This emphasises the need for further high quality studies guided by suggestions for optimised interventions and sensitive assessment tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive Impairment.-Limited evidence from the 2018 PAGAC Scientific Report suggested that for individuals with cognitive impairment, physical activity programs improved physical function, including ADL measures. Two SR/MA examining the relationship between physical activity and physical function in older people with cognitive impairment were identified in the updated search (39,40). One of these meta-analyses (39) comprising 43 trials (N=3,988) reported significant differences between supervised exercise training and control conditions on improvements in performance on the 30-second sit-tostand test (mean difference (MD)=2.1 repetitions; 95% CI: 0.3 to 3.9; 4 trials), step length (MD=5 cm; 95% CI: 2 to 8; 5 trials), Berg Balance Scale (MD=3.6 points; 95% CI: 0.3 to 7.0; 6 trials), functional reach (MD=3.9 cm; 95% CI: 2.2 to 5.5; 6 trials), TUG test (MD=−1 second; 95% CI: −2 to 0; 11 trials), walking speed (MD=0.13 m/s; 95% CI: 0.03 to 0.24; 7 trials), and the 6MWT (MD=50 m; 95% CI: 18 to 81; 7 trials) in this population.…”
Section: Physical Activity and Physical Function In Older People Withmentioning
confidence: 99%
“…Automaticity is the ability to perform motor and cognitive functions simultaneously without a decline of performance in either task. The automaticity of this dual task (DT) performance has been shown to be significantly decreased in those with AD (Ansai et al 2017), and slow walking speed during DT gait has been shown to be associated with and predictive of falls, presence of mild cognitive impairment (MCI)-a precursor to AD and other dementias, and the progression of dementia in people MCI (Goncalves et al 2018;Lowe et al 2019;MacAulay et al 2014MacAulay et al , 2015MacAulay et al ,2017Montero-Odasso et al 2017).…”
Section: Introductionmentioning
confidence: 99%